2018
DOI: 10.1016/j.ijcha.2018.02.001
|View full text |Cite|
|
Sign up to set email alerts
|

Reporting of coronary artery calcification on chest CT studies in breast cancer patients at high risk of cancer therapy related cardiac events

Abstract: BackgroundThe identification of coronary artery calcification (CAC) detected coincidentally on chest CT exams could assist in cardiovascular risk assessment but may not be reported consistently on clinical studies. Cardiovascular risk factor stratification is important to predict short term cardiac events during cancer therapy and long term cardiac event free survival in cancer patients. We sought to determine the prevalence of CAC and clinical reporting rates in a cohort of cancer patients at high risk of can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 24 publications
0
17
2
1
Order By: Relevance
“…Our study also shows that there was significant underutilization of statins in AF patients and that reporting CAC in CTPV reports did not improve the statin therapy pattern. The reporting rate of CAC on CTPV in our study of 92.8% was higher than in prior studies showing the reporting of CAC to be 18.6%-69% on CT clinical reports [17][18][19]. This excellent reporting ratio can be explained by the fact that all CTPVs in this study were read by cardiologists who were trained in cardiac CT and aware of the clinical importance of CAC detection.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Our study also shows that there was significant underutilization of statins in AF patients and that reporting CAC in CTPV reports did not improve the statin therapy pattern. The reporting rate of CAC on CTPV in our study of 92.8% was higher than in prior studies showing the reporting of CAC to be 18.6%-69% on CT clinical reports [17][18][19]. This excellent reporting ratio can be explained by the fact that all CTPVs in this study were read by cardiologists who were trained in cardiac CT and aware of the clinical importance of CAC detection.…”
Section: Discussioncontrasting
confidence: 71%
“…While CAC is typically detected and quantified using a dedicated non-contrast CT CAC scan with electrocardiogram(ECG)-gating, CAC detected using contrast-enhanced cardiac CT correlates strongly with dedicated CAC scans [12][13][14][15]. Evaluating and reporting CAC on all non-contrast chest CT scans is recommended, though it is not commonly reported [16][17][18][19]. CAC was incorporated into the 2013 guidelines as one of the few other tests that function as a risk modifier in subjects at intermediate risk and was explicitly incorporated into the CV risk prediction guidelines in 2018 [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that CV disease and breast cancer have several overlapping risk factors, such as obesity and smoking, meanwhile cardiovascular events (CVEs) is considered as one of the major causes of death in breast cancer patients undergoing chemotherapy, and AIs may contribute to the development of CVEs [7, 5052]. For older women, the CV disease may pose a greater mortality threat than breast cancer itself [7].…”
Section: Discussionmentioning
confidence: 99%
“…It is found that CV disease and breast cancer have several overlapping risk factors, such as obesity and smoking, meanwhile cardiovascular events (CVEs) is considered as one of the major causes of death in breast cancer patients undergoing chemotherapy, and AIs may contribute to the development of CVEs [7,[49][50][51]. For older women, the CV disease may pose a greater mortality threat than breast cancer itself [7].…”
Section: Discussionmentioning
confidence: 99%